Detachment in capillary adhesion: The relative roles of tilting and separation - Butler, M; Vella, D (Oxford University Press, 2020)
We study the dynamics of detachment in 2D capillary adhesion by considering a plate that is initially attached to a flat, rigid substrate via the surface tension of a bridging liquid droplet. In particular, we focus on the effect of allowing the plate to tilt freely during its subsequent motion. A linear stability analysis shows that small perturbations from equilibrium decouple into two modes: one in which the plate separates from the substrate, remaining parallel, and another in which it tilts, simultaneously causing the bridging droplet to migrate. If the initial tilt perturbation is of a similar magnitude to (or bigger than) the separation perturbation, then the presence of this second tilting mode can significantly alter the dynamics. Indeed, this tilting mechanism changes the ultimate fate of the plate: depending on the size of the plate and the initial perturbation, the plate may anomalously detach. We discuss this observation in relation to previous experiments on a 3D system that showed a qualitatively similar anomalous detachment.